PENGARUH KOMPENSASI DAN PROMOSI JABATAN TERHADAP TURNOVER INTENTION DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Amaliya Dwi Anjani; Kusuma Chandra Kirana; Syamsul Hadi (Jurnal Pendidikan Ekonomi (JURKAMI), 2023)
The purpose of this study was to investigate the effect of the effect of compensation and promotion on turnover intention with job satisfaction as an intervening variable in CV. Danagung D'briquettes Cegokan Wonolelo Bantul Yogyakarta. This research is quantitative. The population in this study were all employees of CV. Danagung D'briquettes Cegokan Wonolelo Bantul with 60 employees. The sampling method in this study used non-probability sampling with the Saturated Technique. Data was collected by distributing questionnaires. The data analysis technique used is the inner model with the bootstrapping method. The data that has been obtained is processed using SmartPLS 3.0. The results of this study indicate that compensation has a positive effect on job satisfaction. Promotion has a positive effect on job satisfaction. Job satisfaction has a negative effect on Turnover intention. Compensation has a negative effect on Turnover intention. Position Promotion has a negative effect on Turnover intention. Job satisfaction mediates the relationship between compensation and promotion to turnover intention